Do racial differences exist in the association between pregnancy-induced hypertension and breast cancer risk?. (3rd April 2017) - Lin, Li-Te; Hu, Li-Yu; Tang, Pei-Ling; Tsui, Kuan-Hao; Cheng, Jiin-Tsuey; Huang, Wei-Chun; Chang, Hong-Tai
ABSTRACT: Background : Previous studies investigating the relationship between pregnancy-induced hypertension (PIH) and breast cancer risk have yielded inconsistent results. Unlike numerous Western studies, studies have reported that PIH may be a risk factor for breast cancer in Western Asian women. To confirm these results, we designed a retrospective population-based cohort study to assess the relationship between PIH and subsequent risk for breast cancer in Taiwan. Methods : Patients with newly diagnosed PIH were selected from the Taiwan National Health Insurance Research Database (NHIRD), and a 1:4 matched cohort of women without PIH based on age and the year of delivery was randomly selected from the same database as the comparison group. The incidence of new-onset breast cancer was assessed in both cohorts. Results : Among the 23.3 million individuals registered in the NHIRD, 26, 638 patients with PIH and 106, 552 matched controls were identified. The incidence rate of breast cancer was higher in patients with PIH than in the matched controls (incidence rate ratio = 1.09, 95% confidence interval [CI] = 1.09–1.10, p < 0.0001). However, the Kaplan–Meier analysis revealed a similar cumulative incidence rate of breast cancer between the PIH and comparison cohorts (log-rank p = 0.4303). Moreover, results from a multivariate analysis indicated that PIH was not a statistically significant independent risk factor for breast cancer (adjusted hazard ratio = 1.10, 95% CI = 0.87–1.39, p = 0.4247). Conclusions : The present study demonstrated no significant temporal relationship between PIH and risk for subsequent breast cancer in Eastern Asian women.